Efficacy of artemether-lumefantrine, artesunate-amodiaquine, dihydroartemisinin-piperaquine and artesunate-pyronaridine for the treatment of uncomplicated Plasmodium falciparum malaria in Mozambique, 2022 - Abel Nhama; Arlindo Chidimatembue; Lídia Nhamussua; Quique Bassat; Clemente da Silva; Arsénio Nhacolo; Paulo Arnaldo; Crizolgo Salvador; Annette Cassy; Baltazar Candrinho; Mércia Dimene; Eva Carvalho; et al. (Malaria Journal)
Abstract Background Artemether-lumefantrine (AL) and artesunate-amodiaquine (AS-AQ) are the first-line treatments against malaria in Mozambique. Dihydroartemisinin-piperaquine (DP) has been used in-country for mass drug administration campaigns, and artesunate-pyronaridine (AS-PY) is considered an alternative drug to delay AL resistance in the country. To assess whether AL and AS-AQ remain efficacious and to confirm that DP and AS-PY are potential alternatives for uncomplicated malaria treatment, an in vivo therapeutic efficacy study was conducted in Mozambique at five sentinel sites. Methods This study was conducted in the districts of Montepuez (AL), Dondo (AL and AS-AQ), Mopeia (AL and AS-PY), Moatize (AL and AS-AQ), and Massinga (AL and DP) following the 2009 World Health Organization (WHO)-recommended protocol. Patients aged 6 months to 11 years with uncomplicated Plasmodium falciparum malaria (1000–200,000 parasites/µl) were enrolled, followed, and assessed for 28 days (AL and AS-AQ) or 42 days (DP and AS-PY). Genotyping for msp1/msp2/poly-α markers and match counting via the WHO/Medicines for Malaria Venture (MMV) 3/3 algorithm were used to differentiate recrudescences from new infections. The primary outcome was polymerase chain reaction corrected efficacy for each drug. Results In total, 828 participants were enrolled in the four study arms: AL (462), AS-AQ (183), DP (91), and AS-PY (92). Among the recruited participants, 10.2% (85/828) were lost to follow-up or withdrew, and 60 had recurrent malaria infections, 55 of which were considered new infections and five recrudescences. Day 28 corrected AL efficacy was 100% (95% CI 94.3–100) in Massinga, 100% in Dondo, 100% (95% CI 95.5–100) in Moatize, 97.63% (95% CI 94.4–100) in Mopeia, and 98.68% (95% CI 96.2–100) in Montepuez. Day 28 corrected AS-AQ efficacy was 100% in Dondo and 100% (95% CI 95.4–100) in Moatize. For DP, the corrected efficacy on day 42 was 100% (95% CI 94.1–100) in Massinga, and that on day 42 was 97.75% (95% CI 94.7–100) in Mopeia. All drugs were well tolerated, with adverse events reported in less than 2% of the participants. Conclusion AL and AS-AQ remain effective, as their efficacy remained above the 90% WHO-recommended cut-off. DP and AS-PY also showed therapeutic efficacy above the WHO-acceptable cut-off and could be used as first-line treatments when needed. All four artemisinin-based combinations were well tolerated, with minimal safety concerns. Trial registration Clinicaltrials.gov: NCT05343312.